The Residents’ Perception of the Impacts of Tourism in Porto - Carvalho, João M. S. (2021)
The tourism phenomenon interferes directly in the life of individuals, so the study of the impacts of tourism has become an area of interest, namely associated with the concept of societal sustainability. This paper analyses not only the residents’ perceptions about the economic, social and ecological impacts of tourism in Porto, but also their attitudes towards tourism and tourists. In addition, it was considered a new variable recently introduced in the literature regarding the concept of support to tourism in a behavioural approach. Thus, this study adopts a more comprehensive plan by developing the sequence of ‘perceptions—attitudes—behaviours’ of residents. Considering the nature of the research, the methodology used consisted of the application of a questionnaire survey to a sample of 62 residents in the municipality of Porto. The results of this study indicate that the residents value more the economic component, fol- lowed by the social dimension, and have a less formed opinion about the environmental impacts of tourism. Although the residents show positive atti- tudes towards tourism and tourists, they do not provide behavioural support to tourism development. This exploratory analysis of the residents’ perceptions, attitudes and behaviours to support the tourist development in Porto makes an important contribution to the development of sustainable tourism planning and management in this region.